Prevalence of laryngopharyngeal reflux in adult population using 24 hours ambulatory dual probe pH monitoring - L., Manoj Kumar; K. H., Anand; N., Raadhika Shree (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Laryngopharyngeal reflux disease is an under diagnosed condition due to unavailability of the diagnostic tool that is dual probe pH monitoring and is on the rise in adult population according to El Serag by 4% every year since 1976. Methods: Adult patients coming to the outpatient department between April 2017 to April 2018 were evaluated using reflux symptom index score (RSI). Score greater than 13 were suggestive of laryngopharyngeal reflux and patients underwent 24 hours ambulatory dual probe pH monitoring. 7 or more reflux events in study period were diagnostic of laryngopharygeal reflux. Results: 3000 adult patients were screened for RSI and 1756 (58.3%) had scored greater than 13. Among these patients 893 patients had 7 or more reflux events in pH monitoring. We found a prevalence of 29.76% in our study population. Conclusions: Prevalence laryngopharyngeal reflux disease needs to assess periodically at regular intervals to create more awareness of the disease and patient education thus preventing from causing chronic illnesses.